Nanosensors: Recent perspectives on attainments and future promise of downstream applications. (June 2022) - Adam, Tijjani; C.B. Gopinath, Subash
Abstract: Nano Sensors are sensing devices with a dimension of less than or equal to 100 nm. They are incredibly tiny devices that transform physical, chemical, or biological substances into detectable signals. Because of this device's capacity to detect physical and chemical changes, nanotechnology has emerged as a technology of choice in a variety of industries. The device provides efficient and cost-effective methods for detecting and measuring chemical and physical characteristics. This overview discusses the status of Nano Sensors, as well as their accomplishments and potential applications toward downstream targets in medical, security, agriculture as well in Covid-19 detection. The paper provides a summary and critical analysis of various architectures (structures) employed in the development and use of Nano Sensors. Surface engineering is used to generate diverse chemistries for both general and specialised purposes. We derived fresh findings from available data on the mechanism, prospective development of various structures, approaches, and applications, and highlighted the contrasts and similarities in their characteristics and working processes. The review further summarised ability and future expected of this sensor in dealing with the various challenges where different nano sensors, types, fabrication techniques and applications with highlighted novelties of these techniques and applications are presented. Graphical Abstract: ga1